Improving Problem Solving Ability of 8th Grade Student through The Problem based Learning Model - Sri Fadila Andesa; Suci Fitriani (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2022)
Mathematics learning motivation and students' capacity for problem-solving are still below expectations. The majority of students have difficulty with mathematical issues that are presented as word problems and non-routine problems. This study sought to ascertain whether the Problem Based Learning model enhanced students' capacity for problem-solving and learning motivation. This research was a classroom action research (CAR). This CAR focused on the students of SMP N 8 Banda Aceh's capacity for problem solving. Researchers in this study applied the Problem Based Learning model to all of the learning tasks from cycle 1 to cycle The result showed that The learning outcomes of students studying fractions in have improved using Problem Based Learning Model.